Risk Management in Pinisi Relaxation Using Analytical Hierarchy Process - Rahardjo, Wisnumurti; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
Pinisi Relaxation is a massage parlor that was established in September 2012, and located in the city of Bandung and Sukabumi. Along with the passage of a new company, there are many events that can cost the company, both in terms of financial and non-financial. To be able to cope with such events, Pinisi Relaxation could use risk management approach, as well as the use of Analytical Hierarchy Process in selecting alternative needed to handle the risks. Risk identification in Pinisi Relaxation divided into business risk, financial risk, operational risk, marketing risk, and human resource risk. All risks will be placed in a risk map that reflects the position of any risks inherent in Pinisi Relaxation. The next process is to mitigate the risks inherent in Pinisi Relaxation through analysis of theory and concepts related to conditions in Pinisi Relaxation. Results of analysis for risk mitigation alternatives will then be selected through the Analytical Hierarchy Process to produce the best alternative to handle the risks. Criteria that must be met to handle the risks in Pinisi Relaxation are divided over the cost, effectiveness, and time, in which each of these criteria have different comparisons. Through the process of the analysis, there would be the alternatives that required by Pinisi Relaxation to handle the risks. Each entity in the company should be able to do the alternatives that have been selected in accordance with their respective duties. In addition, the risk management process should always be reviewed and controlled in order to avoid the things that could cost the company if it the risk treatment doesnâ€™t run in an appropriate way.Â Keywords: Pinisi Relaxation, Risk Management, Analytical Hierarchy Process